Beat Tracking in Musical Recordings with Neural Networks - Henkel, Magnus (My University, 2019)
Beat tracking refers to the automated detection of the beat in musical recordings. Two neural network architectures are trained and evaluated for this task.
The beat tracking process is divided into four stages: audio preprocessing, network training, peak-picking and beat detection. In the practical part, two network architectures (CNN and RNN) are trained and evaluated.
Keywords: Titulo: Beat Tracking in Musical Recordings with Neural Networks; Redes Neuronales; Procesamiento de Audio; Computación; Aprendizaje Automático; Machine Learning; Neural Networks; Audio Processing